The influence of social pressure on the mental health of the final-year students at Tadulako University - Sari, Kartini Kartika; Silalahi, Micha Felayati; Puswiartika, Dhevy; Rasido, Ikhlas (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study investigates the influence of social pressure on the mental health of final-year students at Tadulako University using a quantitative survey design with a saturated sample of 800 participants. Data were collected through Likert-scale questionnaires comprising 20 items on social pressure and 38 items on mental health, and subsequently analyzed using descriptive statistics and simple linear regression. The results indicate that students generally experienced high to very high levels of social pressure, while their mental health also fell within high to very high categories. Regression analysis produced the model Y = 32,782 + 0,422X, with a significance value of 0,000 and t = 1,211, confirming a positive and significant effect of social pressure on mental health. The coefficient of determination (R² = 0,948) demonstrates that social pressure explains 15,7% of the variance in mental health, with the remaining 84,3% attributed to other factors. These findings highlight the need for enhanced social support, counseling, and effective coping strategies to mitigate psychological burdens among final-year students